Design of Improved Flow-Focusing Microchannel with Constricted Continuous Phase Inlet and Study of Fluid Flow Characteristics - Zhaohui Wang; Weibing Ding; Yiwei Fan; Jian Wang; Jie Chen; Hongxia Wang (Micromachines, 2022)
This paper proposed an improved flow-focusing microchannel with a constricted continuous phase inlet to increase microbubble generation frequency and reduce microbubbles’ diameter. The design variables were obtained by Latin hypercube sampling, and the radial basis function (RBF) surrogate model was used to establish the relationship between the objective function (microbubble diameter and generation frequency) and the design variables. Moreover, the optimized design of the nondominated sorting genetic algorithm II (NSGA-II) algorithm was carried out. Finally, the optimization results were verified by numerical simulations and compared with those of traditional microchannels. The results showed that dripping and squeezing regimes existed in the two microchannels. The constricted continuous phase inlet enhanced the flow-focusing effect of the improved microchannel. The diameter of microbubbles obtained from the improved microchannel was reduced from 2.8141 to 1.6949 μm, and the generation frequency was increased from 64.077 to 175.438 kHz at the same capillary numbers (Ca) compared with the traditional microchannel. According to the fitted linear function, it is known that the slope of decreasing microbubble diameter with increasing Ca number and the slope of increasing generation frequency with increasing Ca number are greater in the improved microchannel compared with those in the traditional microchannel.